1976
DOI: 10.1029/gl003i005p00261
|View full text |Cite
|
Sign up to set email alerts
|

Height variation of wind speed and wind distributions statistics

Abstract: For use in various wind engineering applications (e.g. wind energy conversion, wind loads on structures, air pollution transport) it is desirable to have a consistent relationship by which to project height variations of both "instantaneous" (e.g. few minute average) winds and parameters of the wind speed probability distribution. The power law V2/V1 = (Z2/Z1)n is often used for height projection of wind profiles, with the exponent n sometimes taken as depending on surface conditions or on atmospheric stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
167
0
9

Year Published

1979
1979
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(181 citation statements)
references
References 2 publications
5
167
0
9
Order By: Relevance
“…Justus and Mikhail, 1976;Hennessey, 1977;Pavia and O'Brien, 1986;Wei, 2010). The function can be expressed as follows:…”
Section: Wind Speed Distributionmentioning
confidence: 99%
“…Justus and Mikhail, 1976;Hennessey, 1977;Pavia and O'Brien, 1986;Wei, 2010). The function can be expressed as follows:…”
Section: Wind Speed Distributionmentioning
confidence: 99%
“…In connection with the development of wind power after the energy crisis in 1973, Justus and Mikhail (1976) suggested a parametrization of the wind-speed probability distribution in terms of the Weibull distribution, described by its scale and shape parameters. The parametrization was based on a universal power law of the vertical wind-speed profile proposed by Zimmer et al (1975), but was limited to heights of 100 m and was soon found (Doran and Verholek 1978) to lead to significant errors.…”
Section: Introductionmentioning
confidence: 99%
“…Most often the wind speed at a meteorology station is measured along a tower at different elevations, and it is desired to be able to find the wind profile at this station for further wind loadings or energy calculations. Some researchers have employed the Weibull pdf for empirical wind speed relative frequency distribution (histogram), and a set of formulas are derived for the extrapolation of the Weibull pdf parameters [15][16][17][18]. In general, two-parameter Weibull pdf of wind speed, P(V ), is given as,…”
Section: Weibull Distribution Parameter Extrapolationmentioning
confidence: 99%
“…The k value can best be estimated by using the approximate relationship for (14) as given by Justus and Mikhail [17], that is:…”
Section: Weibull Distribution Parameter Extrapolationmentioning
confidence: 99%